2022
DOI: 10.1021/acs.langmuir.1c02682
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sporopollenin Shell Interfacial Properties in Protein Adsorption

Abstract: Sporopollenin shells isolated from natural pollen grains have received attention in translational and applied research in diverse fields of drug delivery, vaccine delivery, and wastewater remediation. However, little is known about the sporopollenin shell's potential as an adsorbent. Herein, we have isolated sporopollenin shells from four structurally diverse pollen species, black walnut, marsh elder, mugwort, and silver birch, to study protein adsorption onto sporopollenin shells. We investigated three major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Because of its unique features, such as cytocompatibility, 35 large cavities for drug cargo, and a tough protecting layer, SP is being researched heavily in drug delivery, 36 besides other applications. 37 However, its application in catalysis is still at an infant stage. 38 While the exact basic monomeric unit structure of sporopollenin is still under investigation and debatable, many studies have suggested that it is composed of aliphatic-polyketide-derived polyvinyl alcohol units and 7-O-p-coumaroylated C16 aliphatic units, crosslinked through a distinctive dioxane moiety featuring functional groups such as hydroxyl, epoxide, and acetal, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its unique features, such as cytocompatibility, 35 large cavities for drug cargo, and a tough protecting layer, SP is being researched heavily in drug delivery, 36 besides other applications. 37 However, its application in catalysis is still at an infant stage. 38 While the exact basic monomeric unit structure of sporopollenin is still under investigation and debatable, many studies have suggested that it is composed of aliphatic-polyketide-derived polyvinyl alcohol units and 7-O-p-coumaroylated C16 aliphatic units, crosslinked through a distinctive dioxane moiety featuring functional groups such as hydroxyl, epoxide, and acetal, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Natural pollens have been employed in many biomedical applications. [11,12] According to the various morphologies of pollens from different species, their potential application value has been constantly explored. Take the pollens of sunflowers for instance, the complex three-dimensional (3D) structure with spikes and nanopores on their surface makes them potential carriers for a variety of molecular drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme is often used as a model for interface interactions because it is easily obtainable, has intriguing biophysical properties (often proteins are negative, rather than positive 18 ), and has a useful antimicrobial activity. 19 24 Therefore, it is expected that an improved understanding of lysozyme–material interactions could provide hints for applications beyond the study of bioinspired mineralization. 25 27 …”
Section: Introductionmentioning
confidence: 99%